An empirical study of Asian stock volatility using stochastic volatility factor model: Factor analysis and forecasting - Silvia S. W. Lui (Queen Mary University of London, Department of Economics, 2006)
This paper is an empirical study of Asian stock volatility using stochastic volatility factor (SVF) model of Cipollini and Kapetanios (2005). We adopt their approach to carry out factor analysis and to forecast volatility. Our results show some Asian factors exhibit long memory that is in line with existing empirical findings in financial volatility. However, their local-factor SVF model is not powerful enough in forecasting Asian volatility. This has led us to propose an extension to a multi-factor SVF model. We also discuss how to produce forecast using this multi-factor model.
Keywords: C32; C33; C53; G15; 330; Stochastic volatility; Local-factor model; Multi-factor model; Principal components; Forecasting